KONTRADIKSI DALAM ISTIâMALUL HAQ (TAâASUF), PERSPEKTIF HUKUM ISLAM - Mukharram, M. Tamyiz (Islamic University of Indonesia, 2003)
Islam guarantees and protects individual rights. The guarantees and protects are regarded as an important part to obtain the basic objectives of Syariâa. The freedom to use the rights. However, is not unlimited. Islam maintains limitations to avoid contradiction occures between the implementation of individual rights and otherâs. The abuse of rights, in fiqh sense, called taâasuf. Taâasuw may accures in politic, economic, social, cultural fields, and particulary in patent right. This articles attempts to elaborate Islamic law point of view on the contradiction my occures in patent right and some abstracles that Islamic law experts have to find out the solution.